Comparative Transcriptome Analysis Reveals Substantial Tissue Specificity in Human Aortic Valve. (January 2016) - Wang, Jun; Wang, Ying; Gu, Weidong; Ni, Buqing; Sun, Haoliang; Yu, Tong; Gu, Wanjun; Chen, Liang; Shao, Yongfeng
RNA sequencing (RNA-seq) has revolutionary roles in transcriptome identification and quantification of different types of tissues and cells in many organisms. Although numerous RNA-seq data derived from many types of human tissues and cell lines, little is known on the transcriptome repertoire of human aortic valve. In this study, we sequenced the total RNA prepared from two calcified human aortic valves and reported the whole transcriptome of human aortic valve. Integrating RNA-seq data of 13 human tissues from Human Body Map 2 Project, we constructed a transcriptome repertoire of human tissues, including 19, 505 protein-coding genes and 4, 948 long intergenic noncoding RNAs (lincRNAs). Among them, 263 lincRNAs were identified as novel noncoding transcripts in our data. By comparing transcriptome data among different human tissues, we observed substantial tissue specificity of RNA transcripts, both protein-coding genes and lincRNAs, in human aortic valve. Further analysis revealed that aortic valve-specific lincRNAs were more likely to be recently derived from repetitive elements in the primate lineage, but were less likely to be conserved at the nucleotide level. Expression profiling analysis showed significant lower expression levels of aortic valve-specific protein-coding genes and lincRNA genes, when compared with genes that were universally expressed in various tissues. Isoform-level expression analysis also showed that a majority of mRNA genes had a major isoform expressed in the human aortic valve. To our knowledge, this is the first comparative transcriptome analysis between human aortic valve and other human tissues. Our results are helpful to understand the transcriptome diversity of human tissues and the underlying mechanisms that drive tissue specificity of protein-coding genes and lincRNAs in human aortic valve.